Owning, Using, and Renting: Some Simple Economics of the “Sharing Economy” - Filippas, Apostolos; Horton, John J.; Zeckhauser, Richard J. (Management Science, 2020)
New Internet-based “sharing-economy” markets enable consumer-owners to rent out their durable goods to nonowners. We model such markets and explore their equilibria both in the short run, in which ownership decisions are fixed, and in the long run, in which ownership decisions can be changed. We find that sharing-economy markets always expand consumption and increase surplus, but may increase or decrease ownership. Regardless, ownership is decoupled from individual preferences in the long run, as the rental rates and the purchase prices of goods become equal. If there are costs of bringing unused capacity to the market, they are partially passed through, creating a bias toward ownership. To test our theoretical work empirically, we conduct a survey of consumers, finding broad support for our modeling assumptions. The survey also allows us to offer a partial decomposition of the bring-to-market costs, based on attributes that make a good more or less amenable to being shared. This paper was accepted by Joshua Gans, business strategy.